PEMBELAJARAN MUSIKTERPADU: Pengamatan Peran Gamelan dalam Pembentukan Perilaku dan Pengembangan Kemampuan DasarAnak Usia Prasekolah - Budi Raharja (LPMPP Universitas Negeri Yogyakarta, 2004)
This article discusses the role ofthegamelan, the traditional set of Javanese musical instruments, in helping to shape the character and develop the basic skills of children at kindergarten. It has been made possible by involying a group ofthem in activities related to the instruments. They have beengiven training in nembang(singingtraditional Javanese songs), playing the musical instruments to acco'mpany it, and also role-playing with the accompaniment ofsuch music. The themes ofthe songs and plays have been in line with 'those prescribed for the teaching-learning process at kindergarten. A comparison has afterwards been made between their achievement before the training and that after the training. The result shows that the above-mentioned activities have helped the children develop their language-related behavior, cognitive power, basic life skills, and physical condition. Their role-playing in children's singing games has helped them master speech while their direct involvement with the musical instruments has helped them understand the concept ofnumber, know letters and practice reading, comprehend rhythm and tempo in music, and learn cooperation in group work. Key words: education, music, motivation, effective learning.